Epilithic Diatom Abundance Study in the Batang Kuranji River in Padang City, West Sumatra - Murni, Mida Yulia (Advances in Tropical Biodiversity and Environmental Sciences, 2020)
A study about abundant of epilithic diatom was conducted on 2017 in Kuranji River. The objective of this study was to clarify species and abundant of epilithic diatom in Batang Kuranji River. Samples were collected in 3 stations by purposive sampling and brushing method. The results showed that totally 82 species in 22 genera had been found. The total abundant of epilithic diatom was 15139,26 individual/cm 2 . The highest abundance of epilithic diatom was found in station I (Batu Busuak) and the lowest in station III (Sawah Liek). Synedra sp and Fragillaria sp were dominant group of diatoms which are found in almost all sites. Some physical and chemical water quality parameters were showed that Batang Kuranji River were polluted slightly by organic and inorganic materials.